2021
DOI: 10.1002/adem.202100152
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in the Design of Novel β‐Titanium Alloys Using Integrated Theory, Computer Simulation, and Advanced Characterization

Abstract: Metastable β‐titanium (β‐Ti) alloys, because of their combination of high specific strength, superior corrosion resistance, and excellent biocompatibility, have found increasingly widespread application in aerospace, automobile, biomedical, and chemical industries. Many different pathways, available for phase transformation and deformation between a high‐temperature β and a low‐temperature α phase, provide ample opportunities to engineer the desired microstructure through thermal mechanical processing for opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 120 publications
0
4
0
Order By: Relevance
“…Please do not adjust margins Please do not adjust margins field model, developed by the present authors 33,46 , accounts for multiple transport mechanisms operating during sintering, including surface transport (such as surface diffusion, lattice diffusion from the particle surface to the sintering neck, vapor transport through evaporation and condensation) and bulk transport (such as grain boundary (GB) diffusion and lattice diffusion from the GB to the pore). The latter transport mechanism leads to densification (i.e., reduction in particle spacing) while the former does not.…”
Section: Simulated Sinteringmentioning
confidence: 99%
See 1 more Smart Citation
“…Please do not adjust margins Please do not adjust margins field model, developed by the present authors 33,46 , accounts for multiple transport mechanisms operating during sintering, including surface transport (such as surface diffusion, lattice diffusion from the particle surface to the sintering neck, vapor transport through evaporation and condensation) and bulk transport (such as grain boundary (GB) diffusion and lattice diffusion from the GB to the pore). The latter transport mechanism leads to densification (i.e., reduction in particle spacing) while the former does not.…”
Section: Simulated Sinteringmentioning
confidence: 99%
“…To gain a better understanding of the pore evolution and densication kinetics during sintering, a multi-phase eld model was also employed to study the microstructure (including solid grains and pore) evolution from a green-body with the same particle size distribution as the realistic pellets informed by experimental SEM characterization. The phase-eld model, developed by the present authors, 33,46 accounts for multiple transport mechanisms operating during sintering, including surface transport (such as surface diffusion, lattice diffusion from the particle surface to the sintering neck, vapor transport through evaporation and condensation) and bulk transport (such as grain boundary (GB) diffusion and lattice diffusion from the GB to the pore). The latter transport mechanism leads to densication (i.e., reduction in particle spacing) while the former does not.…”
Section: Simulated Sinteringmentioning
confidence: 99%
“…[ 27 ] As a summary, {332}<113> twinning has attracted increasing attention in the design of metastable β–Ti alloys with simultaneous improvement of strength and ductility. [ 5,27–29 ]…”
Section: Introductionmentioning
confidence: 99%
“…[27] As a summary, {332}<113> twinning has attracted increasing attention in the design of metastable β-Ti alloys with simultaneous improvement of strength and ductility. [5,[27][28][29] Recently, pre-twinning has been used as an effective method to enhance the strength of metallic materials. [30][31][32][33] For example, Xin et al reported that the introduction of f1012g twins in a prerolled AZ31 alloy can cause a significant increase in yield strength compared to the as-received alloy.…”
mentioning
confidence: 99%